Arsenic trioxide and all-trans retinoic acid combination therapy for the treatment of high-risk acute promyelocytic leukemia: results from the APOLLO trial : hematologic malignancy - Platzbecker, Uwe; Adès, Lionel; Montesinos, Pau; Ammatuna, Emanuele; Fenaux, Pierre; Baldus, Claudia; Bernardi, Massimo; Berthon, Céline; Bocchia, Monica; Bonmati, Caroline; Borlenghi, Erika; Bornhäuser, Martin; et al. (Journal of clinical oncology, 2025)
Purpose - The phase III APOLLO trial prospectively compared the efficacy of arsenic trioxide (ATO) in combination with all-trans retinoic acid (ATRA) regimen (ATRA and ATO [ATRA-ATO]) plus low-dose idarubicin versus standard ATRA plus anthracycline-based chemotherapy (ATRA-CHT) regimen (ie, ATRA and idarubicin regimen) in patients with high-risk acute promyelocytic leukemia (APL; EudraCT 2015-01151-68; ClinicalTrials.gov identifier: NCT02688140). - Methods - Adult patients with newly diagnosed high-risk APL in the ATRA-ATO arm received ATO 0.15 mg/kg once daily and ATRA 45 mg/m2 twice daily until complete remission (CR), with two doses of idarubicin 12 mg/m2 on days 1 and 3, followed by consolidation therapy (four ATRA-ATO cycles). Patients in the ATRA-CHT arm received induction with ATRA 45 mg/m2 twice daily and idarubicin 12 mg/m2 once daily on days 1, 3, 5, and 7, followed by three cycles of chemotherapy-based consolidation and 2 years of maintenance therapy. The primary study end point was event-free survival (EFS) at 2 years. - Results - As of July 2022, 133 eligible patients had received either ATRA-ATO (n = 68) or ATRA-CHT (n = 65). The study was discontinued prematurely because of slow accrual during the COVID-19 pandemic. After a median follow-up of 37 months (range, 1.7-88.6 months), 2-year EFS was 88% in the ATRA-ATO arm and 71% in the ATRA-CHT arm (HR, 0.4 [95% CI, 0.17 to 0.92]; log-rank test P = .02). At a median of 7.8 and 12.1 months from achievement of CR, molecular relapse occurred in one (1.5%) ATRA-ATO patient versus eight (12.3%) ATRA-CHT patients (P = .014). Overall, 32% and 68% of patients receiving ATRA-ATO and ATRA-CHT, respectively, reported serious treatment-emergent adverse events (P < .01). - Conclusion - The results of the APOLLO trial support the use of ATO and ATRA for the treatment of newly diagnosed patients with high-risk APL.